How Cultural Hotels Create Cultural Meaning: With the Role of Interior Design, Art Experience, Hotel Brand Image, and Staying Experience - Moch Sabur; Rofialdi Ramadhan Djamin; Willy Arafah (Politeknik Siber Cerdika Internasional, 2026)
Background: Cultural hotels have emerged as a distinctive segment of the hospitality industry, integrating local cultural values, traditional aesthetics, and symbolic experiences into the guest stay. In Jakarta, where cultural diversity and urban tourism intersect, cultural hotels serve as important sites for the transmission of local identity and meaning. Despite growing interest in culture-based hospitality, empirical studies examining how interior design, art experience, brand image, and marketing strategies collectively shape cultural meaning among hotel guests remain limited, particularly in the Indonesian context. Objective: This study aims to analyze the influence of interior design, perceived art experience, cultural marketing, hotel brand image, and pleasant staying experience on the formation of cultural meaning among guests of cultural hotels in Jakarta. Methods: This study uses a quantitative explanatory research approach. Data were collected through an online survey distributed to 270 respondents who had stayed at a cultural hotel in Jakarta, using a purposive sampling technique. Data analysis was conducted through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis using SPSS. Results: The results indicate that all independent variables have a positive and significant effect on cultural meaning. These findings suggest that culture-based experiences, reflected through interior design, perceived art experience, cultural marketing, hotel brand image, and pleasant staying experience, play a crucial role in shaping the cultural meaning perceived by guests. Conclusion: This study concludes that all five independent variables—interior design, perceived art experience, cultural marketing, hotel brand image, and pleasant staying experience—significantly and positively influence cultural meaning among guests of cultural hotels in Jakarta. Perceived art experience and pleasant staying experience demonstrated the strongest contributions. These findings imply that cultural hotels must holistically integrate aesthetic, symbolic, and experiential elements to enhance cultural meaning. This study contributes to the literature on cultural tourism and service marketing by empirically validating a meaning-transfer framework in the Indonesian hospitality context.